Compliance in Filling Surgical Safety Checklist at The Central Surgical Installation - Noprianty, Richa; Putri, Riski Anisa; Manuopo, Hilmy (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2024)
Background: One indicator to reduce unwanted events in the operating room is to implement the filling of the surgical safety checklist (SSC) sheet.Objective: The purpose of the study was to identify the level of compliance in filling SSC in the sign in, time out, and sign out phases at the central surgical installation.Methods: The research method uses quantitative descriptive with an observational study approach. The sampling technique used purposive sampling with 72 respondents. The research instrument uses SSC sheets according to Hospital’s SOP which refer to World Health Organization (WHO) standards. This research has received ethical approval from RS X with number 070/17/Ethical Clearance/RS X/III/2023. Data collection was carried out by researchers and research assistants, namely anesthesia students who were practicing at the hospital. In addition, this data was also checked by the anesthesia management team before analysis. Data analysis uses univariate analysis with the form of data presentation using categorical data, the results of which are frequency distributions and percentages using computer software.Results: The results showed that in the SSC filling the sign in phase had the highest non-compliance rate on aspiration risk items and complicating factors (63%), while in the time out phase the highest non-compliance rate on the estimated length of operation item (90%), and in the sign out phase the highest non-compliance rate on verbal confirmation items of instrument completeness, the number of gauze or sponges, number of needles/other sharp tools (68%).Conclusion: The filling of SSC sheets has not been fully carried out and the filling is done at the end after the operation is completed due to the workload and lack of labor resources. In addition, to speed up the process of transferring patients from the pre-anesthesia room to the operating table. It is expected that the surgery team (doctors, anesthesiologists, and surgical nurses) can be used as input so that the filling of the SSC sheet can be applied according to the sign in, time out, and sign out phases to minimize the possibility of surgical risk errors.